2017
DOI: 10.22317/jcms.06201702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum cystatin C in early diabetic nephropathy in type 2 Iraqi diabetic patients

Abstract: Objective This study aimed to find the effect of serum Cystatin C in early diabetic nephropathy. Method This study was conducted in Al Kindy Teaching Hospital during the period from December, 2015 to June, 2016. The study included 90 subjects (30 males and 30 females) with diabetic type 2 and 30 healthy control. Age is between 30 and 70 years. Patients were with no history of liver disease, thyroid or other endocrine diseases through clinical interviewing. They were divided in to three groups. 30 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…For glomerular filtration markers, cystatin-C and creatinine clearance, the current results found that cystatin-C significantly increased in the P group and SL group as compared with both SM and control groups, which illustrates the role of long-term sitagliptin treatment in preventing GFR decline in the SM group. The current results are in accordance with those of Al-Saedy et al, who showed the reverse relationship between cystatin-C and GFR and recommended the use of cystatin-C as an accurate marker of high sensitivity to detect changes in GFR. Moreover, serum cystatin-C level can be utilized as a predictable marker for kidney damage in T2DM with microalbuminuria.…”
Section: Discussionsupporting
confidence: 93%
“…For glomerular filtration markers, cystatin-C and creatinine clearance, the current results found that cystatin-C significantly increased in the P group and SL group as compared with both SM and control groups, which illustrates the role of long-term sitagliptin treatment in preventing GFR decline in the SM group. The current results are in accordance with those of Al-Saedy et al, who showed the reverse relationship between cystatin-C and GFR and recommended the use of cystatin-C as an accurate marker of high sensitivity to detect changes in GFR. Moreover, serum cystatin-C level can be utilized as a predictable marker for kidney damage in T2DM with microalbuminuria.…”
Section: Discussionsupporting
confidence: 93%